Antiretroviral drug adherence : what happens when patients are hospitalized to medical wards and level one wards in Dr. George Mukhari hospital, Pretoria, and they are on Highly Active Antiretroviral Therapy [HAART] - Nkosi, Thandi Hazel (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPhil)--Stellenbosch University, 2010.